DDX17 is involved in DNA damage repair and modifies FUS toxicity in an RGG-domain dependent manner. - Fortuna, T.R.; Kour, S.; Anderson, E.N.; Ward, C.; Rajasundaram, D.; Donnelly, C.J.; Hermann, A.; Wyne, H.; Shewmaker, F.; Pandey, U.B. (Acta Neuropathologica, 2021)
Mutations in the RNA binding protein, Fused in Sarcoma (FUS), lead to amyotrophic lateral sclerosis (ALS), the most frequent form of motor neuron disease. Cytoplasmic aggregation and defective DNA repair machinery are etiologically linked to mutant FUS-associated ALS. Although FUS is involved in numerous aspects of RNA processing, little is understood about the pathophysiological mechanisms of mutant FUS. Here, we employed RNA-sequencing technology in Drosophila brains expressing FUS to identify significantly altered genes and pathways involved in FUS-mediated neurodegeneration. We observed the expression levels of DEAD-Box Helicase 17 (DDX17) to be significantly downregulated in response to mutant FUS in Drosophila and human cell lines. Mutant FUS recruits nuclear DDX17 into cytoplasmic stress granules and physically interacts with DDX17 through the RGG1 domain of FUS. Ectopic expression of DDX17 reduces cytoplasmic mislocalization and sequestration of mutant FUS into cytoplasmic stress granules. We identified DDX17 as a novel regulator of the DNA damage response pathway whose upregulation repairs defective DNA damage repair machinery caused by mutant neuronal FUS ALS. In addition, we show DDX17 is a novel modifier of FUS-mediated neurodegeneration in vivo. Our findings indicate DDX17 is downregulated in response to mutant FUS, and restoration of DDX17 levels suppresses FUS-mediated neuropathogenesis and toxicity in vivo.